2.4 GHz CMOS Power Amplifier with Mode-Locking Structure to Enhance Gain - Changhyun Lee; Changkun Park (The Scientific World Journal)
We propose a mode-locking method optimized for the cascode structure of an RF CMOS power amplifier. To maximize the advantage of the typical mode-locking method in the cascode structure, the input of the cross-coupled transistor is modified from that of a typical mode-locking structure. To prove the feasibility of the proposed structure, we designed a 2.4 GHz CMOS power amplifier with a 0.18 μm RFCMOS process for polar transmitter applications. The measured power added efficiency is 34.9%, while the saturated output power is 23.32 dBm. The designed chip size is 1.4×0.6 mm2.